2010
DOI: 10.1055/s-0030-1248282
|View full text |Cite
|
Sign up to set email alerts
|

Early Course of Berardinelli-Seip Congenital Lipodystrophy (BSCL)

Abstract: Berardinelli-Seip congenital lipodystrophy (BSCL) is a very rare autosomal recessive disease. In the described patient diagnostic relevant symptoms developed at 3 week age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Additionally, a CGL case series involving a subgroup of seven patients from Oman aged between 0 and 4 years, reported that all patients had hepatomegaly, with splenomegaly (67%), acanthosis nigricans (67%), acromegaloid features (67%) and hypertriglyceridemia (71%) also detected [ 23 ]. Results from the MENA cohort and other studies therefore suggest that metabolic and organ system abnormalities in CGL can develop around the time of onset of fat loss and may be detectable during infancy [ 23 , 48 51 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, a CGL case series involving a subgroup of seven patients from Oman aged between 0 and 4 years, reported that all patients had hepatomegaly, with splenomegaly (67%), acanthosis nigricans (67%), acromegaloid features (67%) and hypertriglyceridemia (71%) also detected [ 23 ]. Results from the MENA cohort and other studies therefore suggest that metabolic and organ system abnormalities in CGL can develop around the time of onset of fat loss and may be detectable during infancy [ 23 , 48 51 ].…”
Section: Discussionmentioning
confidence: 98%
“…Of the patients who were diagnosed at or before 1 year of age, 44% and 33% presented with acromegaloid features and acanthosis nigricans, respectively, 77% had at least one organ abnormality, 23% had HbA1c > 6.5% and 24% had triglycerides > 5.65 mmol/L. The development of the organ system and metabolic complications during early childhood has been documented in several CGL cases studies [ 23 , 48 51 ]. For example, Eltermann et al (2010) reported severe metabolic complications including elevated AST (104 IU/L), ALT (203 IU/L), GGT (508 IU/L), and triglycerides of 23.7 mmol/L (= 2100 mg/dL) in a 3-week-old patient with CGL2 of Turkish origin [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation